Gastric Emptying Is Not Delayed and Does Not Correlate With Attenuated Postprandial Blood Flow Increase in Medicated Patients With Early Parkinson's Disease - Siebner, Thomas Hartwig; Fuglsang, Stefan; Madelung, Christopher Fugl; Løkkegaard, Annemette; Bendtsen, Flemming; Hove, Jens Dahlgaard; Damgaard, Morten; Madsen, Jan Lysgård; Siebner, Hartwig Roman (Frontiers in Neurology, 2022)
BACKGROUND: We have recently used phase-contrast magnetic resonance imaging (PC-MRI) to demonstrate an attenuated postprandial blood flow response in the superior mesenteric artery (SMA) in 23 medicated patients with Parkinson’s disease (PD) compared to 23 age- and sex-matched healthy controls (Siebner TH et al. J Parkinsons Dis 2021;11:545-557). OBJECTIVE: To investigate in a sub-sample of the original cohort whether the observed blood flow response in SMA after oral food intake is related to a delay in gastric emptying. METHODS: We studied 15 patients with PD in an "ON-medication" state with a mean disease duration of 3.9 ± 2.2 years and 15 healthy age- and sex-matched individuals. Participants underwent dynamic gastric scintigraphy 0, 30, 60, 120, 180 and 240 minutes after the intake of a standardized radiolabeled test meal. Gastric emptying was compared between groups. Fourteen of the 15 PD patients and 12 of the 15 healthy control subjects had previously undergone serial postprandial PC-MRI measurements. In these individuals, we tested for a relationship between gastric emptying and postprandial blood flow response in the SMA. RESULTS: The dynamics of gastric emptying did not differ between groups (p=0.68). There was substantial inter-subject variability of gastric emptying in PD patients and healthy participants. Only a single PD patient had delayed gastric emptying. In those participants who had undergone PC-MRI, postprandial increase in SMA blood flow was attenuated in PD compared to healthy controls as reported previously (p<0.006). Gastric emptying did not correlate with the timing and amplitude of postprandial blood flow increase in SMA. CONCLUSION: Our preliminary results, obtained in a small group of early-stage PD patients who continued their usual dopamine replacement therapy, suggest that variations in gastric emptying after solid meal intake is within the normal range in the majority of cases. There is also no evidence for a tight relationship between the attenuated postprandial blood flow response in the SMA and normal variations in gastric emptying.